The Role of Context and Discussion for Improvement Students' Oral and Written Mathematical Communication - Darto Darto; Kartono Kartono; Widowati Widowati; Mulyono Mulyono (Universitas Negeri Semarang, 2022)
Problems in learning mathematics on aspect communication mathematical oral and write student still low . this _ caused lack of given opportunity to student for argue , present ideas and his opinion in study math . Ability communication mathematical oral could be measured with indicator communication mathematical oral like presentation , discussion , whereas ability communication mathematical writing could be measured with write answer , known from question , what is being asked in question , and give conclusion in settlement question end . Role context and discussion in learning mathematics so important for increase ability communication mathematical oral and write student . Destination from study this is for increase ability communication mathematical oral and write through role context and discussion . Sample in study this is student class VIIE SMP Negeri 3 Base drain Regency Pelalawan Riau Province totaled 28 students . Method in study this is study qualitative . Result from study this is role context and discussion could increase ability communication mathematical oral and writing at a good level . With thereby could concluded that role context and discussion could increase ability communication mathematical good in a manner oral nor write.